Fabrication and Study of the Performance Characteristics of a Semi-automated Cablegation Irrigation System - Jayasudha, V; Chandrasekaran, D (Journal of Agricultural Engineering, 2001)
An attempt has been made to study the performance of a cablegation irrigation system. Cablegation supplies the water through a multi-outlet pipeline, pipe being laid on a precise gradient, and discharge is controlled by a moving plug inside the pipeline. The cablegation system's efficiency on water front advance pattern along the furrow length and moisture storage distribution beneath the soil surface were studied for two different treatments and compared with the conventional flood irrigation. The graphical representation of water front advance and moisture distribution are given. The analysis revealed that system covered the entire furrow length within 49 minutes of advancement time whereas the conventional irrigation took an additional 2.39 minutes to cover the balance furrow length besides consuming 61.5 minutes of irrigation time to supply the total volume of water required per furrow. The moisture distribution was 20 percent more than the continuous furrow.